A genome-wide perspective about the diversity and demographic history of seven Spanish goat breeds. Issue 1 (December 2016) - Manunza, Arianna; Noce, Antonia; Serradilla, Juan; Goyache, Félix; Martínez, Amparo; Capote, Juan; Delgado, Juan; Jordana, Jordi; Muñoz, Eva; Molina, Antonio; Landi, Vincenzo; Pons, Agueda; et al.
Abstract Background The main goal of the current work was to infer the demographic history of seven Spanish goat breeds (Malagueña, Murciano-Granadina, Florida, Palmera, Mallorquina, Bermeya and Blanca de Rasquera) based on genome-wide diversity data generated with the Illumina Goat SNP50 BeadChip (population size, N = 176). Five additional populations from Europe (Saanen and Carpathian) and Africa (Tunisian, Djallonké and Sahel) were also included in this analysis (N = 80) for comparative purposes. Results Our results show that the genetic background of Spanish goats traces back mainly to European breeds although signs of North African admixture were detected in two Andalusian breeds (Malagueña and Murciano-Granadina). In general, observed and expected heterozygosities were quite similar across the seven Spanish goat breeds under analysis irrespective of their population size and conservation status. For the Mallorquina and Blanca de Rasquera breeds, which have suffered strong population declines during the past decades, we observed increased frequencies of large-sized (ROH), a finding that is consistent with recent inbreeding. In contrast, a substantial part of the genome of the Palmera goat breed comprised short ROH, which suggests a strong and ancient founder effect. Conclusions Admixture with African goats, genetic drift and inbreeding have had different effects across the seven Spanish goat breeds analysed in the current work. This has generated distinct patterns of genome-wide diversity that provide new clues about the demographic history of these populations.